Sustainability Management in Industrial Companies (American Journal of Management, 2024)
Industrial companies have numerous avenues for implementing sustainability innovations, which can significantly reduce the negative ecological impact of their activities. In this context, a variety of options for action and types of innovation are available to companies at different system levels. These range from innovations in the material and energy flows used for processing, procedural and product innovations, through to comprehensive organisational and functional innovations at the consumer and user level. There are numerous interdependencies between the different levels and types of innovation.
Keywords: management; production & product ecology; function orientation; system levels; types of innovation